Analysis of the Patients Who Admitted To A Turkish Emergency Department During COVID-19 Pandemic: Patients in pandemic hospital - Altınbilek, Ertuğrul; Öztürk, Derya; Atasoy, Ceren; Özlem, Miray; Yılmaz, Fevzi; kavalci, Cemil (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: In this study, it was aimed to review patients who presented to a Turkish emergency department (ED) with fever and at least one symptom and finding of acute respiratory infection (cough, shortness of breath) in Sisli Hamidiye Etfal Education and Research Hospital Tertiary Medical Care Center during COVID-19 pandemic.Methods: This retrospective, descriptive, observational study included patients presented between March 10, 2020 and April 25, 2020. The patients were classified into two groups according to RT-PCR test result: RT-PCR (+) and RT-PCR (-). The demographic characteristics and clinical endpoint-related factors were analyzed in the patients.Results: The study included 840 patients; 461 men (54.9%) and 379 women (45.1%). RT-PCR test was positive in 345 patients (41.0%). The most common comorbidity was hypertension (HT) in 119 patients (34.5%); followed by diabetes mellitus (DM) in 61 patients (18.3%). At time of ED presentation, there was mild clinical manifestation in 72.2%, whereas moderate in 21.7% and severe in 6.1% of patients with positive RT-PCR testing. Of the patients with positive RT-PCR testing, 64 patients (18.6%) were discharged from ED while 255 patients (73.9%) were admitted to COVID clinic and 26 were admitted to COVID intensive care unit (ICU). Of the patients admitted, 299 patients (86.7%) were discharged while 46 patients (13.3%) died due to multi-organ failure (MOF) (50%), acute respiratory distress syndrome (ARDS) (32.6%), acute pulmonary embolism (APE) (10.9%) and acute coronary syndrome (ACS) (6.5%).Conclusions: The RT-PCR positivity rate seemed lower in our study when compared to literature. In addition, mortality rate was lower in our study when compared to other countries.